Reprezentatív marketing-versenyképességi pillanatkép 2009-ben a magyar kis- és középvállalatok körében - Szabó, György (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Carried out recently Companies’ competitiveness is a central subject worldwide for economic development. It is a vital issue for today’s Hungarian small and medium enterprises as the driver for future competitiveness. With the knowledge about companies’ competitiveness one can determine aspects and preferences for developing competitiveness. The study that has been but has not been closed yet in 2009 ’serves as an informative basis for the analysis of the situation, in order to allow Hungarian firms’ positions to be learnt and directions for development to be determined and clarified.